HUBUNGAN JARAK PANDANG, PENCAHAYAAN DAN FREKUENSI ISTIRAHAT MATA DENGAN KELUHAN COMPUTER VISION SYNDROME PADA PENGGUNA KOMPUTER DI KANTOR X KOTA BATAM TAHUN 2026 - Marisina Butar Butar; Noviyanti; Andi Sarbiah; Noviyanti Noviyanti (Journal of Innovation Research and Knowledge, 2026)
Computer Vision Syndrome (CVS) is an eye disorder caused by prolonged computer use and may be influenced by viewing distance, lighting intensity, and eye rest frequency. This study aimed to determine the relationship between viewing distance, lighting, and eye rest frequency with Computer Vision Syndrome complaints among computer users at Office X Batam City in 2026. This study used an analytical observational design with a cross-sectional approach involving 55 respondents selected using total sampling. Data were collected through measurement and questionnaires, then analyzed using Chi-Square test. Results showed significant relationships between viewing distance (p=0.009), lighting (p=0.047), and eye rest frequency (p=0.026) with CVS complaints. It was concluded that these factors were associated with Computer Vision Syndrome complaints.